Pharmacokinetic interaction of green tea beverage containing cyclodextrins and high concentration catechins with P-glycoprotein substrates in LLC-GA5-COL150 cells in vitro and in the small intestine of rats in vivo. (4th October 2017) - Oda, Keisuke; Murakami, Teruo
Abstract: Objectives: Possible interaction of green tea beverage (GT) containing cyclodextrins and high concentration catechins, a drinking water, with P-glycoprotein (P-gp) substrates was examined in vitro and in vivo. Methods: Effects of GT on the uptake of rhodamine 123 by LLC-GA5-COL150 cells and intestinal efflux of rhodamine 123 from blood, intestinal absorption of quinidine from ileum loop and oral absorption of digoxin were examined in rats. Effects of GT and GT components on digoxin solubility were also examined. Key findings: Green tea increased the uptake of rhodamine 123 by LLC-GA5-COL150 cells, suppressed the intestinal efflux of rhodamine 123 from blood and increased the absorption of quinidine in the ileum of rats. Also, GT increased the solubility of digoxin, and ingestion of GT significantly increased the oral absorption of digoxin given at a high dose in rats. Conclusions: Green tea suppressed the P-gp-mediated efflux transport of hydrophilic compounds and increased the solubility of lipophilic compounds. Thus, GT may cause interaction with various P-gp substrates, due to the combined effects of catechins and cyclodextrins. Especially, cyclodextrin alone can cause interaction with various low-solubility compounds in vivo. In taking low-solubility drugs including low-solubility P-gp substrates, cyclodextrin-containing foods and beverages such as GT should be avoided.